Effect of Solid State Fermentation Biomass on Nutrients intake, Digestibility and Microbial Protein Synthesis in Lactating Buffaloes - Patel, Kishan P. P; Katole, Shrikant B.; Pandya, P. R.; Patel, Srushti; Murty, D. Srinivas (Indian Journal of Animal Nutrition, 2020)
Increasing livestock population with limited availability of feed resources requires a paradigm shift in implementing newer arena of nutritional research which empowers efficient utilization of available low quality feed resources. The objective of present study was to evaluate the effect of Solid State Fermentation (SSF) biomass on nutrients intake and digestibility of lactating buffaloes. Treatments were based on comparison between basal diet (provided by farmers of private dairy in Sojitra village) supplemented with or without SSF biomass having known quantity of fibrolytic enzymes at rate of 4% of Dry Matter Intake (DMI). 20 lactating buffaloes (2nd -3rd week post-calving) were selected and randomly assigned to one of the either treatment for duration of 139 days. Towards the end of feeding trial provision was made for individual fecal collection from buffaloes to measure nutrients digestibilities. SSF supplementation has not resulted in any significant improvement in Dry Matter (DM) and Crude Protein (CP) intake, but intake of Digestible Crude Protein (DCP) and Total Digestible Nutrients (TDN) intake was significantly (p<0.05) improved under SSF supplemental group. Supplementation of SSF biomass has significantly (p<0.01) improved the digestibility of proximate components (Dry matter, Organic matter, Crude fiber, Ether extract and Nitrogen free extract) and also improved Crude protein digestibility significantly (p<0.05). Digestibility of fiber fractions had also shown significant (p<0.01) improvement due to SSF supplementation. Notable (but non-significant) increase in microbial protein synthesis (on basis of purine derivatives) was also observed in SSF supplemental group. Supplementing SSF biomass as crude fermented product with fibrolytic enzymes has resulted in improvement in digestibility of nutrients without affecting DM intake of lactating buffaloes which signifies that SSF biomass helps in effective utilization of feeds and potentiation of energy availability for productive performance. Â Â Â